Merger Perusahaan: Menggabungkan Kekuatan untuk Keunggulan Kompetitif - Tri Nurhayati (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The increasingly competitive business environment requires companies to continually seek strategies to strengthen their market position and enhance their competitive advantage. Mergers are one effective strategy, where two or more business entities combine to form a stronger entity. This article examines the reasons behind merger decisions, the expected benefits, and the challenges faced during the integration process. However, challenges such as the integration of corporate cultures, technological systems, and regulatory compliance become critical factors that need to be well managed. Through the analysis of various successful cases and real-world challenges, this article explains how mergers can increase market share, create economies of scale, diversify products and services, and provide better access to technology and resources.